A statistical method for pitch measurement and evaluation. Issue 5 (March 2020) - Cai, Xiaoyu; Wu, Junjie; Li, Yuan; Zhang, Xuedian; Lei, Lihua; Wei, Jiasi
Abstract: Nano grating is one of the common standards in micro-nano scale dimensional measurement and calibration. Errors terming from the measurement system, measurement procedure, data process and the object (specimen) affect the grating evaluation result. Either more precise measurement systems or optimization in methodology is underdeveloped to realize more accurate measurement. In this study, a measuring procedure, using scanning probe microscopy to measure 1D grating, is put forward firstly, mainly to reduce cosine error. Then a measuring statistical model is established based on the statistical characteristics of measurement system, terming from both the machine and the standard. By measuring the grating area for enough times, the mathematical equations are fitted and the statistical characteristic variables, i.e. the mathematical expectation and variance of both the measurement machine error and the grating are to be solved. Practically, the grating is measured in roughly the same area for several times using a nano measurement machine, with unknown error. The grating pitch as well as the errors of the machine stage were evaluated.